Perceptions and Practices of Educational Leadership in Community Schools of Kathmandu Metropolitan City (Pragyaratna प्रज्ञारत्न, 2024)
The purpose of study is to explore the perceptions and practices of educational leadership in community school of Kathmandu Metropolitan City. The study employed a qualitative case study research design to conduct an empirical investigation, involving the participation of head teachers, assistant head teachers, and teachers from community schools. This study examines how instructional strategies, teacher motivation, and engagement are improved in community schools through the use of educational leadership. This study identifies key leadership practices and techniques that foster a productive learning environment through qualitative methods, including interviews, observations, and document analysis. The verbal data were collected, transcribed, categorized, and organized into themes. The results indicate that success cannot be achieved by one person alone; collaborative teamwork is essential. Educational leadership should act as a facilitator, fostering effective partnerships with stakeholders. Growth and development cannot occur without motivation, and educational leadership must build trust and unity among stakeholders. Educational leadership should emphasize praise, respect for parents, and cooperation to strengthen partnerships among teachers, students, and parents. The study emphasizes the role of leadership in creating holistic learning environments that emphasize community engagement. When promoting harmony, accountability, and the use of distributed and transformative leadership, community schools can encourage student progress. The study highlights various leadership philosophies, the influence of social and cultural contexts, and strategies to enhance academic achievement. The findings offer insights to inform educational policy and leadership development programs.